PENGEMBANGAN MODUL PEMBELAJARAN ELEKTRONIK PADA MATERI SENYAWA HIDROKARBON KELAS XI DALAM PEMBUATAN BRIKET LIMBAH KULIT DURIAN (Durio Zibethinus) - Hakmah, Siti; Maulina, Julia; S, Uswatun Hasanah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2022)
This study aims to develop an electronic module on hydrocarbon material using a flipbook application by validating material experts, media experts and providing questionnaires to test student responses. This research was carried out in two locations, namely the MIPA-Chemistry laboratory at the Islamic University of North Sumatra and the MAS Swasta Nurul Islam in Kuta Cane Class XI IPA in the odd semester of 2021. The method used was the Research and Development (R&D) method. Development model The learning device that will be used is the model proposed by Thiagarajan, namely the 4D model (Define, Design, Development, Dissemantion). However, in this research, only up to the development stage (Develop). The instrument used is a material expert validation questionnaire, media expert, and student response questionnaire. The data analysis technique was carried out by collecting the scores obtained from each questionnaire and then calculating the percentage of eligibility and converting the average score of the assessment aspect into a qualitative value. From the results of the study, the average percentage of each aspect, namely material experts and media experts was 3.5% with good and valid categories and student responses of 3.76% with practical and good categories. This shows that the electronic module can used as teaching materials in schools.Keywords: Development, Electronic Learning Module, Hidrokarbon, and Durian Peel Waste Briquettes.